PengaruhPenggunaanSubstrat pada Pengomposan Secara Anaerob Menggunakan Tandan Kosong Kelapa Sawit (TKKS) dari Limbah Media Jamur Merang - Supriyanto Supriyanto (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The anaerobic decomposition process of organic matter in EFB from straw mushroom media waste with the addition of substrates from manur, sludge, EM4 and POME is an alternative treatment of organic material by producing compost and biogas. This study aims to determine the effect of the use of substrate in the composting process of EFB from the waste media of straw mushrooms and the content of chemical nutrients in compost EFB with anaerobic fermentation. The composting process is carried out by inserting EFB in anaerobic bioreactors and adding substrates containing the starter. During the decomposition process observations were carried out every week and every two weeks. The parameters analyzed are temperature, pH, C/N, available P, K-dd and biogas volume. The results showed that the anaerobic organic matter decomposition process carried out for 8 weeks contained the highest biogas production when treated using a substrate from EM4 with a biogas volume of 10L / day with temperatures reaching 30oC having a pH characteristic of 8.79; Nitrogen 1.04 - 1.68%, C-organic 15.30%, C / N 11.71, P-available 0.69 and K-dd 1.13%.